PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN ATLET LARI 3000 METER CLUB JUNIOR ATLETIK PASI RIAU - Muhammad Rozi; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: From the observation and monitoring of the 3000 Meter Club Junior Athletics Sprint Athletes in PASI Riau that the talents and interests possessed by athletes are very large. This is evidenced by the perseverance and perseverance of the athletes in carrying out all the training programs provided by the coach. But from the results of the observations that the author has done at the PASI Riau Athletics Club during training and during the competition, many athletes did not optimally perform athletic movement techniques and quickly experienced fatigue. Especially the middle distance race numbers consist of 800 m, 1500 m and long distance distances of 3000 m and 5000 m and 3000 m steeple chase for boys and girls, while for long distance numbers that is 10,000 m, marathon 42,195 km required good physical condition, because for this distance requires maximum aerobic strength starting from start to finish. The purpose of the study was to find out